2005
DOI: 10.1177/089686080502500614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Administration of Losartan, Prazosin, and Verapamil on Peritoneal Solute Transport in Continuous Ambulatory Peritoneal Dialysis Patients

Abstract: Background Several intraperitoneally administered drugs have been shown to modify transport of peritoneal solute and fluid. Fewer studies, however, have evaluated the effect of orally administered drugs. The present study was performed to evaluate the effects of oral losartan, prazosin, and verapamil on peritoneal membrane transport during a peritoneal equilibration test (PET), as well as the effects on creatinine clearance (CrCl), Kt/V urea, 24-hour protein in drained dialysate, and drained volume. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…After screening of titles/abstracts, 101 full-text articles of potentially relevant studies were acquired. After appraising these articles against study inclusion/exclusion criteria (Supplementary, Table S1), we included 10 RCTs 1214,25,31–36 and 10 non-randomised studies 11,2024,26,37–39 that compared RAAS blockade classes with active control (Table 1). Four RAAS blockade classes were compared with active control—ACEIs, ARBs MRAs, and mixed ACEIs/ARBs, however, no data for DRIs in any outcome of interest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening of titles/abstracts, 101 full-text articles of potentially relevant studies were acquired. After appraising these articles against study inclusion/exclusion criteria (Supplementary, Table S1), we included 10 RCTs 1214,25,31–36 and 10 non-randomised studies 11,2024,26,37–39 that compared RAAS blockade classes with active control (Table 1). Four RAAS blockade classes were compared with active control—ACEIs, ARBs MRAs, and mixed ACEIs/ARBs, however, no data for DRIs in any outcome of interest.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of RAAS blockade in PD patients has not been fully elucidated. Some studies have revealed the protective properties 11–15,19 , whereas others have not 2026 . Previous systematic reviews have shown that ACEIs/ARBs substantially benefit in preserving rGFR in PD patients, while a lack of evidence exist regarding the relative efficacy of MRAs and direct renin inhibitors (DRIs) 2729 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, high concentrations of glucose could bias the estimations of dialysate total protein or albumin concentration-more so during the 3.86% PET than the 2.27% PET. The reported methods of estimation of dialysate protein concentration are heterogeneous (7)(8)(9)(10)13,31,33,(36)(37)(38), although the nephelometry and colorimetric methods are the most common. In general, glucose is not considered to interfere markedly in the estimation of plasma or dialysate protein level, but concentrations as high as those observed during a 3.86% PET may have not been routinely tested for most of the methods.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed that CCBs can have two separate effects on PD: increasing UF and causing chyloperitoneum. CCBs have been reported in the past to have various effects on PD, including increasing peritoneal clearance (4), reducing peritoneal glucose uptake (5,6), and increasing UF (1,6-10). The most commonly studied CCBs in these series were verapamil and diltiazem, or both.…”
Section: Discussionmentioning
confidence: 99%